2017
DOI: 10.1039/c7ta02661g
|View full text |Cite
|
Sign up to set email alerts
|

High flux electroneutral loose nanofiltration membranes based on rapid deposition of polydopamine/polyethyleneimine

Abstract: Tailor-made electroneutral loose nanofiltration membranes for fractionation of the dye/salt mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(82 citation statements)
references
References 51 publications
5
77
0
Order By: Relevance
“…The PEI/piperazine membrane also show higher salt separation with MgCl 2 rejection of >90% with moderate water flux of ≈4.3 L m −2 h −1 bar −1 . A significant amount of research has been carried out to develop loose polymeric nanofiltration membranes to maximize salt passage while rejecting dyes from the salt/dye mixture . For example, Wang et al and Li et al have prepared loose nanofiltration membranes based on crosslinked PEI.…”
Section: Water Permeance and Molecular Separation Behavior Of The Polmentioning
confidence: 99%
See 2 more Smart Citations
“…The PEI/piperazine membrane also show higher salt separation with MgCl 2 rejection of >90% with moderate water flux of ≈4.3 L m −2 h −1 bar −1 . A significant amount of research has been carried out to develop loose polymeric nanofiltration membranes to maximize salt passage while rejecting dyes from the salt/dye mixture . For example, Wang et al and Li et al have prepared loose nanofiltration membranes based on crosslinked PEI.…”
Section: Water Permeance and Molecular Separation Behavior Of The Polmentioning
confidence: 99%
“…A significant amount of research has been carried out to develop loose polymeric nanofiltration membranes to maximize salt passage while rejecting dyes from the salt/dye mixture . For example, Wang et al and Li et al have prepared loose nanofiltration membranes based on crosslinked PEI. They achieved a high rejection (97.1–99.8%) of congo red dye (MW: 696 g mol −1 ) and a low rejection (5–10%) of NaCl and Na 2 SO 4 .…”
Section: Water Permeance and Molecular Separation Behavior Of The Polmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] If the concentration of divalent ions,s pecifically Ca 2+ the attachment of inorganic precipitates onto the membrane, causes deterioration of membrane performance and increased energy consumption. [18][19][20] In conjunction with different composite materials,o thers have improved the performance of nanofiltration by exploring different strategies to modify the surface of nanofiltration membranes, [18][19][20][21] which range from rapid co-deposition of polymers [21] to in situ surface reactions [18] to inkjet printing. A common method of removing Ca 2+ and Mg 2+ through precipitation is the use of sodium carbonate (Na 2 CO 3 )a nd NaOH to produce calcium carbonate (CaCO 3 )a nd magnesium hydroxide (Mg(OH) 2 )salts,which can remove up to 96 and 99 %o fc alcium and magnesium ions,r espectively,f rom the NF permeate.…”
Section: Nanofiltrationmentioning
confidence: 99%
“…Alternatively,insearch of effective methods to eliminate divalent ions,r ecent work on cross-linked layer-by-layer polyelectrolyte nanofiltration hollow fiber membranes by Liu et al [16] and Labban et al [17] has demonstrated the selective rejection of multivalent ions at exceedingly low pressures, showing that advanced NF membranes may be useful for removing scalants from the feed stream without the precipitation step.A dditionally,c arbon nanotube composite and graphene oxide-incorporated polymeric membranes have been shown to exhibit greater mechanical stability and ability to purify water. [18][19][20] In conjunction with different composite materials,o thers have improved the performance of nanofiltration by exploring different strategies to modify the surface of nanofiltration membranes, [18][19][20][21] which range from rapid co-deposition of polymers [21] to in situ surface reactions [18] to inkjet printing. [19] Multiple factors can influence the efficiency of NF systems,i ncluding the operating conditions and membrane configuration.…”
Section: Nanofiltrationmentioning
confidence: 99%